Imaging features of fibrolamellar hepatocellular carcinoma - Ganeshan, Dhakshinamoorthy; Szklaruk, Janio; Kundra, Vikas; Kaseb, Ahmed; Rashid, Asif; Elsayes, Khaled M; Elsayes, Khaled (American journal of roentgenology (1976), 2014)
Fibrolamellar hepatocellular carcinoma (HCC) is a rare primary liver tumor, which significantly differs from conventional HCC. This article reviews the molecular cytogenetics, pathology, imaging features, and management of this relatively rare tumor. Fibrolamellar HCC predominantly occurs in young patients without underlying hepatitis or cirrhosis. Serum α-fetoproteins are not elevated in most cases, and hence imaging plays an important role in diagnosis, staging, and surveillance.